Designing CXCL8-based decoy proteins with strong anti-inflammatory activity in vivo. Issue 5 (17th September 2013) - Falsone, Angelika; Wabitsch, Veronica; Geretti, Elena; Potzinger, Heide; Gerlza, Tanja; Robinson, James; Adage, Tiziana; Teixeira, Mauro M.; Kungl, Andreas J.
Abstract : IL (interleukin)-8 [CXCL8 (CXC chemokine ligand 8)] exerts its role in inflammation by triggering neutrophils via its specific GPCRs (G-protein-coupled receptors), CXCR1 (CXC chemokine receptor 1) and CXCR2, for which additional binding to endothelial HS-GAGs (heparan sulphate-glycosaminoglycans) is required. We present here a novel approach for blocking the CXCL8-related inflammatory cascade by generating dominant-negative CXCL8 mutants with improved GAG-binding affinity and knocked-out CXCR1/CXCR2 activity. These non-signalling CXCL8 decoy proteins are able to displace WT (wild-type) CXCL8 and to prevent CXCR1/CXCR2 signalling thereby interfering with the inflammatory response. We have designed 14 CXCL8 mutants that we subdivided into three classes according to number and site of mutations. The decoys were characterized by IFTs (isothermal fluorescence titrations) and SPR (surface plasmon resonance) to determine GAG affinity. Protein stability and structural changes were evaluated by far-UV CD spectroscopy and knocked-out GPCR response was shown by Boyden chamber and Ca 2+ release assays. From these experiments, CXCL8(Δ6F17KF21KE70KN71K) emerged with the most promising in vitro characteristics. This mutant was therefore further investigated in a murine model of mBSA (methylated BSA)-induced arthritis in mice where it showed strong anti-inflammatory activity. Based on these results, we propose that dominant-negative CXCL8 decoy proteins are a promising class of novel biopharmaceuticals with high therapeutic potential in inflammatory diseases.